Questioning Security Guarantees After the Return of the Former Shia Community: Islam and Human Rights Law Analysis - Saiful Abdullah; Mahmood Ali Suhail Al Maashani; Amancik Amancik; Bambang Sumantri; Moh. Widadun Ni'am (Faculty of Law Universitas Trunojoyo Madura, 2026)
This study aims to examine the mechanisms and systems for restoring the right to security for former Shia adherents who have returned to their hometowns in Sampang Regency. The government must ensure the fulfillment of this right to security in accordance with its commitment to guarantee that there is no harassment or exclusion of former Shia adherents after their return. This study contributes to advancing knowledge and mechanisms for resolving Sunni-Shia conflicts, with a focus on restoring the right to security and equality. This study employs an empirical legal research method with a socio-legal research approach. The study’s findings reveal that disturbances persist, affecting the fulfillment of the right to security following the return of former Shia adherents. Such disturbances include ongoing threats of murder against former Shia adherents if they revert to their former sect. Additionally, strict surveillance by law enforcement officials and the community toward former Shia adherents—whether during religious rituals or their interactions with the general public—results in their freedom to socialize with the community and practice their faith appearing restricted, which has a psychological impact on them. Certainly, these restrictions conflict with the guarantee of religious freedom enshrined in Indonesian national law, Islamic law, and international human rights instruments. This study concludes that the government’s enforcement of the right to security has not yet been fulfilled in the post-conflict Sunni-Shia reconciliation process, and recommends further government policies to ensure the fulfillment of the right to security and the absence of excessive surveillance of former Shia adherents’ activities, particularly religious practices.